Novel measurement method of Brillouin optical correlation domain analysis based on bidirectional detection scheme - Jeong, J.H.; Lee, K.; Lim, S.D.; Song, K.Y.; Jeong, J.-M.; Lee, S.B. (Technical Digest - 2012 17th Opto-Electronics and Communications Conference, OECC 2012, 2012)
We propose and experimentally demonstrate a bidirectional detection scheme in the Brillouin optical correlation domain analysis. The gain and the loss spectra for the probe waves are simultaneously analyzed, which enables the measurement range twice with a half measurement time. ？ 2012 IEEE.